Patterns of multimorbidity in an older population of persons with an intellectual disability: results from the intellectual disability supplement to the Irish longitudinal study on aging (IDS-TILDA). - MCCARRON, MARY; CARROLL, RACHEL; MCCALLION, PHILIP; MCGLINCHEY, EIMEAR; BURKE, EILISH (My University, 2013)
Multimorbidity (2 or more chronic conditions) is being widely studied in older populations and this study explores both the relevance of emerging conceptualizations and the extent to which multimorbidity is a feature of aging in persons with an intellectual disability. Methods Data was generated from wave one of the intellectual disability supplement to the Irish longitudinal study on aging (IDS-TILDA) which included 753 persons with an ID aged 40 years and over. Information on the presence of 12 chronic conditions was collected using a standardized protocol administered in face to face interviews with persons with ID and/or their caregivers. Prevalence of multimorbidity was established and patterns were examined using logistic regression models. The patterns of multimorbidity for people with ID that emerged were then compared with those reported for other older adults. Results Multimorbidity was established for 71% of the IDS-TILDA sample with women at highest risk and rates of multimorbidity was high (63%) even among those aged 40–49 years. Eye disease and mental health problems were most often associated with a second condition and the most prevalent multimorbidity pattern was mental health/neurological disease. Discussion Further investigation, attention to mental health issues and the development of treatment guidelines that recognize chronic condition disease load are critical to mitigating the negative impact of multiple chronic conditions and preventing additional disability in adults with ID as they age. Highlights ► 12 Chronic conditions and pairings of morbidity examined in national random sample. ► People with ID have higher levels of multimorbidity than general population reports. ► Mental health concerns are more significant for people with ID.
PUBLISHED
Keywords: Intellectual disability; Multimorbidity; Aging; Health